2021
DOI: 10.1002/ajim.23245
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of mesothelioma and asbestosis by occupation in a diverse workforce

Abstract: Objective We sought to characterize detailed patterns of mesothelioma and asbestosis incidence in the workforce as part of an occupational disease surveillance program in Ontario, Canada. Methods The Occupational Disease Surveillance System (ODSS) cohort was established using workers' compensation claims data and includes 2.18 million workers employed from 1983 to 2014. Workers were followed for mesothelioma and asbestosis diagnoses in Ontario Cancer Registry, physician, hospital, and ambulatory care records t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…The occupations where we expected to see workers overrepresented in regions with high mesothelioma rates were in the construction trades, mining, processing, and mechanics and repairers consistent with previous research [ 18 ]. Processing is a broad occupational group including workers involved with the processing of materials such as metals, chemicals, petroleum, rubber, plastic, wood and pulp, mineral ore treatment, and textile processing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The occupations where we expected to see workers overrepresented in regions with high mesothelioma rates were in the construction trades, mining, processing, and mechanics and repairers consistent with previous research [ 18 ]. Processing is a broad occupational group including workers involved with the processing of materials such as metals, chemicals, petroleum, rubber, plastic, wood and pulp, mineral ore treatment, and textile processing.…”
Section: Discussionsupporting
confidence: 89%
“…Studies on asbestos consumption have already shown that countries with high usage consistently have higher rates of mortality from mesothelioma [ 16 ], but the risks vary considerably depending on the type of exposure. For example, the primary source of occupational exposure that has been linked to asbestos-related disease has shifted away from the mining sector to other industries such as construction, oil and gas and transportation repair [ 17 , 18 ]. Still, with certain industries being associated with higher asbestos exposure relative to others, it is perhaps unsurprising that trends in mesothelioma incidence would emerge based on geographic differences in the labor force across regions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asbestos has been used since the 19th century, with production skyrocketing during the 20th century due to demand for construction, fireproofing, and insulation . Exposure to asbestos has well-known, well-demonstrated, and long-standing links to adverse health effects, most notably mesothelioma. Despite this, in 2020, global production, primarily in China, Russia, and Kazakhstan, stood at 1.2 million tonnes, with most demand in China and India. ,,, …”
Section: Asbestosmentioning
confidence: 99%
“…For much of the 20th century, though, it was Canada that led global asbestos production, accounting for more than half of all asbestos mined in those 100 years. ,, The vast majority (95%) of asbestos was mined in the province of Quebec, with operations centered around the towns of Asbestos and Thetford Mines. , Production peaked in 1973 at 1.7 million tonnes per year, declining steadily in the years afterward. By 2006, production was at 186,000 tonnes per year …”
Section: Asbestosmentioning
confidence: 99%
“…Various industries have a high risk of asbestos exposure: petroleum refining [12]; pharmaceuticals [13]; chemicals [14]; rubber and plastics [15]; non-metallic products, basic metal manufacturing, metal processing product manufacturing, machinery, and equipment manufacturing [14,16]; electronic parts and electrical equipment manufacturing [17]; shipbuilding [18,19]. In Korea, malignant mesothelioma was reported from the construction [20], shipbuilding, and asbestos textile production industries [21].…”
Section: Introductionmentioning
confidence: 99%